Studi Penggunaan Antibiotika Pada Penderita Rawat Inap Pneumonia (Penelitian Di Sub Departemen Anak Rumkital Dr. Ramelan Surabaya) - Suharjono, Suharjono; T, Yuniati; Sumarno, Sumarno; SJ, Semedi (UI Scholars Hub, 2009)
Pneumonia is an infectious disease that was caused inflammation of acute parenchy-mal compression of the lungs and bacterial exudate from lung tissue on the main from Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, Klebsiella pneumonia, Mycobacterium tuberculosis. Selection of appropriate antibiotic therapy and rational will determine the treatment to avoid the occurrence of bacterial resistance. In addition it is also possible the use of other drugs that can increase the chances of Drug Related Problems (DRP). Pattern of antibiotic use in Rumkital Dr. Ramelan Surabaya has never been done. Studying the pattern use of antibiotics in hospitalized patients with pneumonia in the Sub Department of Pedi-atric Rumkital Dr. Ramelan and related the dose, other therapies, as well as identify the DRP. This research is a method descriptive survey research in the form of a retrospective and descriptive study. Materials research is the Medical Records pa-tients hospitalized with the final diagnosis of pneumonia, starting January 1, 2004 until April 30, 2006 that meet inclusion criteria. Of the study population who account for 50 found 41 patients who fulfilled the inclusion criteria. Antibiotics single most widely accepted patients without comorbidities were ampicillin iv 26.92% (14 patients) and iv sefotaksim 21.15% (11 patients), while the antibiotic combina-tion widely accepted patients is ampicillin iv / po + kloksasilin iv / po 13.46% (7 patients) and kloksasilin iv + ceftriaxone iv 5.77% (3 patients) and the rest other antibiotic combinations. DRP study found 56.9% patients received appropriate anti-biotic dose literature and 43.1% patients receiving doses underdose. Use of antibiotics above is already in ccordance with reference and other therapies. Single antibiotic or combination of 2 antibiotics penicillin and cephalosporin classes often used to treat pneumonia.